PENGARUH PENGETAHUAN TENTANG AKUNTABILITAS, TRANSPARANSI DAN PENGAWASAN TERHADAP PELAKSANAAN DAN PENATAUSAHAAN APBD BERKONSEP VALUE FOR MONEY DENGAN STANDAR AKUNTANSI PEMERINTAH (SAP) DI SKPD KOTA PALEMBANG - Ningsih, Nurul Hutami (Balance : Jurnal Akuntansi dan Bisnis, 2017)
ABSTRACT This study aims to determine and analyse the effect of the knowledge on accountability, transparancy and control in the implementation and administration of APBD and the effect of government accounting standard (moderating variable) on its relation between knowledge on accountability, transparancy and control in the implementation and administration of APBD using value for money concept. The data used is primary data in form of questionairres and secondary data in form of organisational structure, vision and mission of SKPD and government institution of performance accountability report (LAKIP). This study is conducted in 29 SKPD in Palembang on 5 officers of Budget Users/User Items in each SKPD. The data analysis used is Moderated Regression Analysis (MRA) using SPSS v.23. The result shows that the knowledge on accountability (X1) and control (X3) are significant in affecting the implementation and administration of APBD using value for money (Y) concept, meanwhile the knowledge on transparancy (X2) is found to be insignificant. Meanwhile, the government accounting standard (SAP) (X4) is not significant in moderating the relation between the knowledge on accountability (X1), transparancy (X2) and Control (X3) on the implementation and administration of APBD using value for money concept (Y) and the moderating relation found is moderator predictor.  The effect of accountability (x1), transparancey (X2) and control (X3) on the the implementation and administration of APBD using value for money (Y) using Government Accounting Standard are found to be strong in which its adjusted R square is 0.774 or 77.4% meanwhile the rest 23.6% is explain by other factors outside the study